The Basic Of English Phonology: A Literature Review - Yani Lubis; Fatimah Azzahra Siregar; Cut Ria Manisha (Lembaga Pengembangan Kinerja Dosen, 2023)
Abstract: This step-by-step guide provides an overview of English phonology, exploring its definition, scope, and the relationship between phonetics and phonology. It delves into the classification and articulation of English sounds, covering aspects such as place and manner of articulation. The guide emphasizes the use of the International Phonetic Alphabet (IPA) as a standardized system for representing sounds, and provides examples of English vowels and consonants represented by IPA symbols. Understanding English phonology enables learners to improve their pronunciation accuracy, comprehend spoken English more effectively, and enhance their overall communication skills.